Enhanced ionic mobility in Organic Ionic Plastic Crystal – Dendrimer solid electrolytes. (1st September 2015) - Greene, G.W.; Ponzio, F.; Iranipour, N.; Zhu, H.; Seeber, A.; Forsyth, M.; Howlett, P.C.
Abstract: We report the first study of the characterisation of the organic ionic plastic crystal (OIPC) N-ethyl-N-methylpyrrolidinium tetrafluoroborate (C2 mpyrBF4 ) upon mixing with a dendrimer additive. Whereas previous reports of OIPC composite formation (i.e. with ceramics and polymers) have typically reported a decrease in the conductivity when lithium salt had been added, the addition of dendrimer is shown to lead to a substantial enhancement in the lithium containing system, approaching 3 orders of magnitude at 30 °C. Mechanical analysis indicates that dendrimer addition leads to a softer more ductile material while microscopy shows that the dendrimer is uniformly distributed and that the crystal microstructure is substantially disrupted, ultimately adopting a dendritic microstructure at 1 mol% dendrimer content. Thermal analysis indicates a new phase in the lithium OIPC system, the crystallisation of which is suppressed in the presence of dendrimer. Instead, a decrease in the phase transition enthalpies indicates a large increase in the amorphous component of the Lithium OIPC, particularly for the most conductive system -C2 mpyrBF4 + 10 mol% LiBF4 + 0.1 mol% dendrimer. Variable temperature powder X-ray diffraction confirms the presence of a new distinct phase and its absence in the presence of dendrimer. A change in the progression of the thermal phase behaviour of the OIPC in the presence of dendrimer is also shown, exhibiting the phase I (high temperature) structure at temperatures below the phase II-I transition.